2023
DOI: 10.1021/acsomega.3c04857
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic Synthesis of Zinc Oxide Nanoparticles Mediated by the Extract of Terminalia catappa Fruit Pericarp and Its Multifaceted Applications

Cannon Antony Fernandes,
Nameeta Jesudoss M,
Aatika Nizam
et al.

Abstract: Zinc oxide nanoparticles (ZnO-NPs) were biosynthesized by using the pericarp aqueous extract from Terminalia catappa Linn. These NPs were characterized using various analytical techniques such as X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, ultraviolet (UV) spectroscopy, dynamic light scattering (DLS), and scanning electron microscopy (SEM), and XRD studies of the nanoparticles reported mean size as 12.58 nm nanocrystals with highest purity. Further SEM analysis emphasized the nanop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
(119 reference statements)
0
1
1
Order By: Relevance
“…2 D, the ζ-potential analysis revealed that ZnO NPs exhibited a negative charge at − 19.9 ± 0.1663 mV. Significantly, the observed ζ-potential value of the as-prepared NPs in this study surpasses the findings reported in other relevant studies 32 , 37 , 38 . It indicates the relative good stability and dispersity of the green synthesized ZnO NPs, which can be attributed to the presence of functional groups from R. coriaria fruit extract on their surfaces, serving the function of capping and maintaining the stability of NPs.…”
Section: Resultscontrasting
confidence: 71%
See 1 more Smart Citation
“…2 D, the ζ-potential analysis revealed that ZnO NPs exhibited a negative charge at − 19.9 ± 0.1663 mV. Significantly, the observed ζ-potential value of the as-prepared NPs in this study surpasses the findings reported in other relevant studies 32 , 37 , 38 . It indicates the relative good stability and dispersity of the green synthesized ZnO NPs, which can be attributed to the presence of functional groups from R. coriaria fruit extract on their surfaces, serving the function of capping and maintaining the stability of NPs.…”
Section: Resultscontrasting
confidence: 71%
“…Here, the resultant FT-IR spectrum showed a prominent band at 3429 cm −1 , which correlates to the stretching vibration of the OH group of phenolic compounds 31 . Then, two small peaks were noticed at 2926 cm −1 and 2851 cm −1 , corresponding to asymmetrical and symmetrical C–H stretching vibrations of the CH 2 groups, respectively 32 , 33 . A singular band was observed at 2093 cm −1 representing the aromatic overtones, followed by a peak around 1613 cm −1 , which is attributed to the C=C stretching vibration of conjugated alkene groups 34 , 35 .…”
Section: Resultsmentioning
confidence: 99%